Evaluation of microcurrent electrical nerve stimulation (mens) effectiveness on muscle pain in temporomandibular disorders patients - Zuim, Paulo Renato Junqueira [UNESP]; Garcia, Alicio Rosalino [UNESP]; Turcio, Karina Helga Leal [UNESP]; Hamata, Marcelo Matida [UNESP] (FapUNIFESP (SciELO), 2006)
The effect of Microcurrent Electrical Nerve Stimulation (MENS) was evaluated and compared with occlusal splint therapy in temporomandibular disorders (TMD) patients with muscle pain. Twenty TMD patients were divided into four groups. One received occlusal splint therapy and MENS (I); other received splints and placebo MENS (II); the third, only MENS (III) and the last group, placebo MENS (IV). Sensitivity derived from muscle palpation was evaluated using a visual analogue scale. Results were submitted to analysis of variance (p<0.05). There was reduction of pain level in all groups: group I (occlusal splint and MENS) had a 47.7% reduction rate; group II (occlusal splint and placebo MENS), 66.7%; group III (MENS), 49.7% and group IV (placebo MENS), 16.5%. In spite of that, there was no statistical difference (analysis of variance / p<0.05) between MENS and occlusal splint therapy regarding muscle pain reduction in TMD patients after four weeks.
Keywords: Electric stimulation therapy; Occlusal splints; Temporomandibular joint disorders